2020
DOI: 10.1002/jcla.23333
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential metabolite markers for colon cancer and rectal cancer using serum metabolomics

Abstract: Background To determine the metabolic characteristics of patients with colon cancer (CC) and rectal cancer (RC) using gas chromatography‐mass spectrometry (GC‐MS)‐based metabolomics. Methods In this study, serum samples were collected from 22 CC patients and 23 RC patients preoperatively and postoperatively and 45 healthy volunteers (HVs), and subjected to metabolomics analysis by GC‐MS. Differential metabolites in the preoperative RC and CC samples and HVs were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 26 publications
(41 reference statements)
0
29
0
Order By: Relevance
“…Most studies employed a case-control research design, using either a healthy (carcinoma-free) control, adenomatous polyp group, or both. Twenty-one studies compared CRC directly to healthy control [24][25][26]31,33,36,38,39,[42][43][44][45][46][48][49][50][51][52][53][54]56]. Jing et al and Gao et al, conversely, compared CRC patients to an adenomatous polyp control [32,55] while eleven studies utilized CRC, healthy control, and adenomatous polyp groups [28][29][30]34,35,37,40,41,47,57,58].…”
Section: Study Design and Population Characteristicsmentioning
confidence: 99%
“…Most studies employed a case-control research design, using either a healthy (carcinoma-free) control, adenomatous polyp group, or both. Twenty-one studies compared CRC directly to healthy control [24][25][26]31,33,36,38,39,[42][43][44][45][46][48][49][50][51][52][53][54]56]. Jing et al and Gao et al, conversely, compared CRC patients to an adenomatous polyp control [32,55] while eleven studies utilized CRC, healthy control, and adenomatous polyp groups [28][29][30]34,35,37,40,41,47,57,58].…”
Section: Study Design and Population Characteristicsmentioning
confidence: 99%
“…Its diagnosis is very complicated and is currently only based on clinical parameters. Recent reports have shown that middle-aged PSD patients and stroke survivors without depression have different urine metabolism characteristics [14]. Urine metabolomics can be used to identify potential metabolite markers in patients with poststroke depression in middle-aged patients.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC), which encompasses both colon cancer and rectal cancer (RC), is the third most common malignancy worldwide and the second most common cause of cancer-related death, only exceeded by lung cancer [1,2] . Its incidence and mortality have continually increased in recent years [3] . The 5-year survival rate of CRC is still dismal (only 8%-9%) once metastasis has occurred [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence and mortality have continually increased in recent years [3] . The 5-year survival rate of CRC is still dismal (only 8%-9%) once metastasis has occurred [3] . RC accounts for approximately 30% of all CRC cases and is associated with worse clinical outcomes [1,4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation